2014
DOI: 10.1371/journal.pone.0088300
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Non-Small Cell Lung Cancer Based on Copy Number Alterations

Abstract: Lung cancer is one of the leading causes of cancer mortality worldwide and non–small cell lung cancer (NSCLC) accounts for the most part. NSCLC can be further divided into adenocarcinoma (ACA) and squamous cell carcinoma (SCC). It is of great value to distinguish these two subgroups clinically. In this study, we compared the genome-wide copy number alterations (CNAs) patterns of 208 early stage ACA and 93 early stage SCC tumor samples. As a result, 266 CNA probes stood out for better discrimination of ACA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 65 publications
0
29
0
1
Order By: Relevance
“…There was no significant difference in CNVs for these 33 genes according to either gender or smoking history (data not shown). We also compared the performance of our 33‐gene classifier with that of another CNV classifier proposed by Li et al In their study, the classifier consisting of 266 probes was not tested by an independent validation dataset. According to their results, it had a comparable accuracy to our classifier; however, its sensitivity was much lower (0.65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in CNVs for these 33 genes according to either gender or smoking history (data not shown). We also compared the performance of our 33‐gene classifier with that of another CNV classifier proposed by Li et al In their study, the classifier consisting of 266 probes was not tested by an independent validation dataset. According to their results, it had a comparable accuracy to our classifier; however, its sensitivity was much lower (0.65).…”
Section: Discussionmentioning
confidence: 99%
“…All of these facts point to the value of molecular classifications as nonsubjective adjuvant methods. These methods include digital nuclear imaging, mutation analysis, mRNA expression values and various other molecular methods, either alone or in combination …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the CNV pattern between lung adenocarcinoma and squamous cell carcinoma are very different [12] and there are rich mutations and copy number changes in various cancers [13]. Here, we developed a computational method, which successfully uses the information of gene CNV levels to classify six types of cancers -breast adenocarcinoma (BRCA), colon and rectal carcinoma (COAD/READ), glioblastoma multiforme (GBM), kidney renal clear cell carcinoma (KIRC), ovarian serous carcinoma (OV), and uterine corpus endometrial carcinoma (UCEC).…”
Section: Introductionmentioning
confidence: 99%
“…Gene copy number variation (CNV) caused by genomic instability has received attention as a potential parameter for the diagnosis of some tumor subtypes [5]. Among these, it has been found that the CNV-based classifier constructed by comparing the CNV pattern of lung adenocarcinoma and lung squamous cell carcinoma can be used to distinguish two subgroups of non-small cell lung cancer [6]. Xu et al found that CNV analysis could help to identify patients with chronic liver disease who are at high risk of hepatocellular carcinoma (HCC), which is of great value for early monitoring and intervention of HCC.…”
Section: Open Accessmentioning
confidence: 99%